2022
DOI: 10.1101/2022.02.09.22270717
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sero-prevalence of anti-SARS-CoV-2 antibodies in Chattogram Metropolitan Area, Bangladesh

Abstract: Background: Seroprevalence studies of coronavirus disease 2019 (COVID-19) assess the degree of undetected transmission in the community. Different groups, such as healthcare workers (HCWs), garment workers, and others, are deemed vulnerable due to their workplace hazards and immense responsibility. Purpose: The present study was conducted to estimate the seroprevalence of anti-SARS-CoV-2 antibody (IgG) and its association with different explanatory variables. Further, the antibody was quantified to assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Available data from serological tests allow an assessment of the level of circulation of the COVID-19 virus in the population [11]- [16]. In the field of epidemiology, it is important to know in advance the performance of new tests in the field, in order to increase the certainty of the presence or absence of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Available data from serological tests allow an assessment of the level of circulation of the COVID-19 virus in the population [11]- [16]. In the field of epidemiology, it is important to know in advance the performance of new tests in the field, in order to increase the certainty of the presence or absence of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…All of these conditions limit its widespread use in resource-limited countries [10]. Seroepidemiological studies conducted in several countries and particularly in African countries show that positive case statistics based entirely on screening PCR underestimate the true extent of SARS-CoV-2 virus circulation in populations [11]- [16]. On the other hand, a meta-analysis study conducted in 2020 to describe the performance of different antigenic and serological tests in the diagnosis of COVID-19, including 25 diagnostic tests out of a total of 2247 participants, showed that only one diagnostic test had better specificity and sensitivity [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest seroprevalence rates were found in those HCWs who had previous infection(s) and were also vaccinated, but it remains unknown whether this hybrid immunity could translate into protection against the new variants of concern. In order to better understand the level of immunity to actual variants of SARS-CoV-2 and to plan interventions efficiently, the vaccination coverage and seroprevalence of SARS-CoV-2 in both the risk groups and the general community must be assessed in future perspectives [33]. Although our results in HCWs cannot be directly extrapolated to other population groups in Vojvodina and Serbia, it is reasonable to assume that the seroprevalence rates in the general population in our country are relatively high; future studies are warranted to delineate this.…”
Section: Discussionmentioning
confidence: 99%
“…The seroprevalence study [31], which was conducted in Chattogram Metropolitan Area, Bangladesh from February to September 2021 based on the health worker, in and outpatients and garments workers, estimated the overall seroprevalence as 66.99% (95% CI: 63.40%-70.40%). There is another longitudinal cohort study [32] compared the serological response in patients with differing severity of COVID-19 infection.…”
Section: Introductionmentioning
confidence: 99%